Data Envelopment Analysis and Technologies of the Industry of the Future: A Scoping Review - Chodakowska, Ewa (Management and Production Engineering Review, 2026)
Efficiency is a central driver of the industry of the future, serving as both a strategic transformation goal and a cornerstone of smart manufacturing. Modern data-driven approaches have introduced new ways to analyze efficiency in production processes. This study examines the integration of data envelopment analysis (DEA), a widely applied efficiency evaluation method, and Industry 4.0 technologies. A qualitative review was performed using the Web of Science, Scopus, and IEEE Xplore databases, supported by thematic analysis. Key application areas include robotics and internet of things (IoT) systems. The state-of-the-art analysis enabled the identification of strategies for improving performance assessment in human-centric production systems. Promising directions involve hybrid and ensemble models that merge interpretability and transparency with predictive capabilities, autonomy, and largescale data processing. These approaches are strengthened by explainable artificial intelligence (XAI), which enhances user understanding and trust in intelligent decision-making systems.